Pengaruh Strategi Pembelajaran Index Card Match terhadap Prestasi Belajar Siswa Mata Pelajaran Aqidah Akhlak - Choerul Anwar; Salma Avinia (IBTIDA', 2020)
The purpose of this study was to determine the effect of the application of Index Card Match learning strategies on student achievement in Aqidah Akhlak subjects Asma Al-Husna class V MI Ma'arif NU Miru 2017/2018 school year. This type of research is quantitative with correlational research designs. The population in this study is the total number of classes V MI Ma'arif NU Miru with 25 students, while the sample takes the entire population. Methods of collecting observational data, questionnaires and documentation. Data analysis using Product Moment Correlation. The results of this study are the implementation of Index Card Match learning strategies are in the high category there are 15 respondents with a percentage of 60%, student learning achievement Aqeedah Morals in the medium category there are 13 students with a percentage of 52%, there is an influence of Index Card Match learning strategies on learning achievement students of Aqeedah Morals. This is based on the analysis results obtained by the value of rxy = 0.597 and then consulted with the r table at a significant level of 5% and N = 25 is 0.396 so that r count is greater than the r table is 0.597> 0.396 which means there is an influence. The level of influence is strong, because the analysis results obtained rxy value = 0.597 between 0.40-0.599 which means moderate.